Accuracy of paediatric intraosseous needle placement from post mortem imaging. (March 2016) - Jawad, N.; Brown, K.; Sebire, N.J.; Arthurs, O.J.
Abstract: Introduction: Accurate placement of intraosseous needles (ION) is an important part of emergency paediatric resuscitation. The objective of our study was to assess the accuracy of ION placement through post mortem radiological imaging techniques. Methods: We retrospectively reviewed post mortem skeletal surveys (PMSS) performed at our institution in an observational study for the presence or absence of ION on each image of the lower and upper limbs, some of whom had also undergone post mortem CT (PMCT). Placement was documented as correct or incorrect (in soft tissues, through the bone, or within the physis). Results: 115/150 ION were correctly sited (76.7%) in 273 complete PMSS reviewed. 23/35 (65.7%) incorrectly sited ION were within the soft tissues of the leg, 8/35 (22.9%) had gone through the bone, and 4/35 (11.4%) were epiphyseal. 43/66 (65.2%) ION were correctly sited on PMCT, with 65.2%, 30.4% and 4.4% within the soft tissues, gone through the bone and epiphyseal respectively. In 5 discrepant cases, PMCT demonstrated inaccurate ION placement which was termed "correct" on PMSS. Conclusions: Up to a third of ION found at PM imaging are incorrectly placed and lie mostly within the soft tissues of the leg. We highlight this error rate to educate those placing ION in an emergency situation. Highlights: We review the accuracy of intraosseous needle (ION) placement at post mortem imaging. 1/3 ION are incorrectly placed at PM imaging, mostly within the soft tissues. PMCT demonstrated more inaccurate placement than conventional PM radiography. We highlight these errors to educate those placing ION in an emergency situation.